Electromagnetic survey to constraints ore mining exploration in the South-East of Saghro inlier (Eastern Anti-Atlas, Morocco): application of frequency electromagnetic helicopter-borne method - Aafir, Zineb; Hahou, Youssef; Ousaid, Lahcen; Aafir, Soufiane; Courba, Said (Iraqi Journal of Science, 2025)
The Saghro Massif is considered strategic as it contains several localities with high mining indices. The Ikniouen area was chosen in the present work due to its geological characteristics and pre-Cambrian dominant terrain. As well as numerous abandoned mines. To address this problem, an exploration approach based on geophysical methods is required. Geophysics occupies a crucial role in various earth exploration applications. In this paper, we typically utilize the process of pseudo-layer half-space, to determine apparent resistivity from the available electromagnetic (EM) datasets. The DIGHEMv multi-coil, multi-frequency helicopter-borne electromagnetic system was used in a geophysical study carried out southeast of the Saghro inlier. The results revealed three conductor axes, and two significant electromagnetic anomalies in the area, interpreted as indicative of metallic deposits in the subsurface. The most distinct electromagnetic anomalies were detected in the north, center, and southeast parts of the research region. Which were all previously unmined and strongly influenced by secondary faults with coverage of Ediacaran volcanic rocks. Given the established relationship between mineralization and faulting; where the degree of the anomaly is directly correlated with the amount of ore present in the hosted rocks; This location is especially worth exploring.